FAKTOR - FAKTOR YANG MEMPENGARUHI PURCHASING BEHAVIOUR - Reinaldy, Muhamad Genta; Pakpahan, Arnolt Kristian (Universitas Trisakti, 2025)
The objective of the empirical study is to examine and to analyze the effect of Social Media Influencer Credibility on Purchasing Behaviour, both directly and through two mediating variables: Parasocial Relationships and Electronic Word of Mouth (e-WOM). The research focuses on how fashion influencers on TikTok affect indonesian consumer’s purchasing decisions. A quantitative method with a descriptive and data were collected via a questionnaire distributed to 150 active Tiktok users who follow three major fashion influencers: Nathanael Moss, BECE and Cadbury Lemonade. The data were analyzed using Structural Equation Modeling (SEM) with SPSS and AMOS software. The result indicate that Social Media Influencers Credibility has a significant positive effect on both Parasocial Relationships and e-WOM. However, the direct influencers on Purchasing Behaviour is not significant,suggesting that the impact on consumer purchase decisions of mouth. These findings higlight the importance of building influencers credibility through emotional closeness and active engagement to effectively shape Purchasing Behaviour. This study provides practical fo digital marketers’s in designing more impactful social media endorsement strategies.